Did Your Mom Help You Remember?: An Examination of Attorneys' Subtle Questioning About Suggestive Influence to Children Testifying About Child Sexual Abuse. Issue 15 (August 2022) - George, Suzanne St.; Sullivan, Colleen; Wylie, Breanne E.; McWilliams, Kelly; Evans, Angela D.; Stolzenberg, Stacia N.
Researchers studying children's reports of sexual abuse have focused on how questioners overtly assess coaching and truthfulness (e.g., "Did someone tell you what to say?" ). Yet attorneys, and defense attorneys, in particular, may be motivated to ask about suggestive influence and truthfulness in subtle ways, such as with implied meaning (e.g., "Did your mom help you remember?" ). Such questions may be particularly challenging for children, who may interpret statements literally, misunderstanding the suggested meaning. The purpose of this study was to examine and categorize how attorneys' ask about suggestive influence and truthfulness. We wanted to learn how attorneys subtly accuse suggestive influence, and how frequently this occurred. We hypothesized that questions indirectly accusing suggestive influence would be common, and that defense attorneys would ask more subtle questions, and fewer overt questions, than prosecutors. We examined 7, 103 lines of questioning asked by prosecutors and defense attorneys to 64 children testifying about alleged child sexual abuse. We found that 9% of all attorneys' lines of questioning asked about suggestive influence or truthfulness. The majority (66%) of these were indirect accusations. Indirect accusations of suggestive influence spanned a range of subtleties and topics, including addressing conversational influences (e.g., coaching), incidental influences (e.g., witnessing abuse), and others. We also found defense attorneys were less likely than prosecutors to ask about suggestive influence and truthfulness overtly. We conclude that attorneys commonly ask about suggestive influence and truthfulness in subtle ways that developing children may struggle to understand, and which may result in affirmations of influence, even when allegations are true.